PERAN GURU DALAM PENANAMAN KARAKTER FAIRNESS PADA SISWA SEKOLAH DASAR - Riska Maelani; Ratna Purwanty; Dewi Puji Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Character education is being intensively carried out by the government. The government launched various programs to support the optimization of character education in schools, including PPK or Strengthening Character Education. This study intends to describe the teacher's role in inculcating the character of fairness in the students of SD Inpres Mopah Baru, Merauke. This type of research is descriptive qualitative. The subjects in this study were 4 certified teachers. data collection using interview and documentation techniques. Data analysis was conducted to determine the teacher's role in inculcating the character of fairness by conducting member checks and triangulation of sources. The results showed that in the implementation of fairness character planting, there were still students who deviated from the fairness character, including there were students who cheated, there were students who were impatient when waiting in line, there were students who did not want to follow the rules. Teachers try to deal with character deviations that occur by actively providing assistance and approaches to students. The teacher provides assistance to students who have the potential to deviate such as accompanying students when playing and giving special attention to students who have deviated character. Apart from that, teachers also take approaches such as giving advice at the best times for students. This is in line with the teacher's role, which is not only as a teacher but also as an educator who instills moral values ​​and is responsible for the formation of children's character. The teacher's role in inculcating the character of fairness is good.